(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2018)
The objective of the study was to characterize of Boer goats and the Jamunapari goat available in Bangladesh under on-station condition. The study was conducted at Goat and Sheep Research farm of BLRI, Savar, Dhaka from January 2014 to June 2015 and animals were reared under standard intensive management system. The collected data was analyzed by SPSS 17.0 Statistical computer programme. The body coat color of Boer goat was white with reddish-brown head, ears and neck and the body coat color of Jamunapari goats was variety of colors. Both of them had horns but polled Jamunapari goats were also found. The body weight significantly (p<0.001) differed between Boer goat (52.36±5.97 kg) and Jamunapari goat (39.26±3.00 kg). Horn length of Boer goat (19.01±1.29 cm) was significantly (p<0.001) higher than Jamunapari goat (7.98±0.71 cm). Head width and teat length of Jamunapari goat (33.82±0.85 cm and 9.15±0.89 cm) were significantly higher (p<0.05) than Boer goat (30.23±0.63 cm and 5.80±0.87 cm). Rump width significantly (p<0.05) differed between Boer goat (17.87±0.61 cm) and Jamunapari goat (15.19±0.59 cm). The body length, height at wither, chest girth and ear length of Boer goat were 69.96±2.09 cm, 67.98±1.19 cm, 78.39±2.04 cm and 19.43±0.90 cm, respectively where as body length, height at wither, chest girth and ear length of Jamunpari goat were 72.13±1.63 cm, 69.69±1.29 cm, 79.18±2.04 cm and 21.23±0.66 cm, respectively. Phenotype wise Boer goats have distinct meat characteristics than the Jamunapari goats. Asian Australas. J. Biosci. Biotechnol. 2018, 3 (1), 28-32